Fourier-transform infrared spectroscopy with undetected photons from high-gain spontaneous parametric down-conversion - Hashimoto, Kazuki; Horoshko, Dmitri B.; Kolobov, Mikhail I.; Michael, Yoad; Gefen, Ziv; Chekhova, Maria V. (Communications Physics, 2024)
Fourier-transform infrared spectroscopy (FTIR) is an indispensable analytical method that allows label-free identification of substances via fundamental molecular vibrations. However, traditional FTIR spectrometers require mid-infrared (MIR) elements, including low-efficiency MIR photodetectors. SU(1,1) interferometry has previously enabled FTIR with undetected MIR photons via spontaneous parametric down-conversion in the low-parametric-gain regime, where the number of photons per mode is much less than one and sensitive photodetectors are needed. In this work, we develop a high-parametric-gain SU(1,1) interferometer for MIR-range FTIR with undetected photons. Using our method, we demonstrate three major advantages: a high photon number at the interferometer output, a considerably lower photon number at the sample, and improved interference contrast. In addition, we broaden the spectral range of the interferometer by aperiodic poling in the gain medium. Exploiting the broadband SU(1,1) interferometer, we measure and evaluate the MIR absorption spectra of polymers in the 3-μm region.
CRIS-Team Scopus Importer:2024-07-12